Literature review on the potential effects of electromagnetic fields and subsea noise from marine renewable energy developments on Atlantic salmon, sea trout and European eel. Scottish Natural Heritage Commissioned Report - Gill, Andrew B.; Bartlett, Mark D. (Cranfield University, 2011)
Background This report reviews the current state of knowledge with regard to the potential for three fish species of conservation importance, namely Atlantic salmon (Salmo salar), sea trout (Salmo trutta) and European eel (Anguilla anguilla), to be affected by marine renewable energy developments (MRED). The focus is on marine wave and tidal power developments that will generate electricity offshore, which will then be transferred to land by subsea cable. During construction and operation, the marine renewable energy (MRE) devices are expected to cause a number of disturbances to the marine environment including electromagnetic fields (EMF) emissions and subsea sounds (generally referred to as ‘noise'). Such disturbances were assessed to meet the following aims: To determine the current understanding of the effects of EMFs and noise associated with the installation and operation of MREDs, on the behaviour of three species: S. salar, S. trutta and A. anguilla. To determine the gaps in current knowledge and identify research requirements.Main findings The availability and quality of the information on which to base the review was found to be limited with respect to all aspects of the fishes migratory behaviour and activity, both before and after MRE development; this makes it difficult to establish cause and effect. The main findings were: S. salar and A. anguilla can use the earth's magnetic field for orientation and direction finding during migrations. S. trutta juveniles, and close relatives of S. trutta, respond to both the earth's magnetic field and artificial magnetic fields. Current knowledge suggests that EMFs from subsea cables and cabling orientation may interact with migrating eels (and possibly salmonids) if their migration or movement routes take them over the cables, particularly in shallow waters (<20m).The effect, if any, could be a relatively trivial temporary change in swimming direction, or potentially a more serious avoidance response or delay to migration. Whether this will represent a biologically significant effect cannot yet be determined. S. salar, S. trutta and A. anguilla are likely to encounter EMF from subsea cables either during the adult movement phases of life or their early life stages during migration within shallow, coastal waters adjacent to the natal rivers. The subsea noise from MRE devices has not been suitably characterised to determine its acoustic properties and propagation through the coastal waters. MREDs that require pile driving during construction appear to be the most relevant to consider, in addition to the time scale over which pile driving is carried out, for the species under investigation. In the absence of a clear understanding of their response to subsea noise, the specific effects on S. salar, S. trutta and A. anguilla remain very difficult to determine for Scottish waters in relation to tidal and wave power. Based on the studies reviewed, it is suggested that fish that receive high intensity sound pressures (i.e. close proximity to the MRED construction) may be negatively impacted to some degree, whereas those at distances of 100's to 1000's of metres may exhibit behaviour responses, the impact of which is unknown and will be dependent on the received sound. During operation there may be more subtle behavioural effects that should be considered over the life time of the MRED. Whether these effects will represent biologically significant impacts cannot yet be determined. The current assumptions of limited effects are built on an incomplete understanding of how the three species move around their environment and interact with natural and anthropogenic EMF and subsea noise. A number of gaps in understanding exist, principally whether S. salar, S. trutta and A. anguilla respond to the EMF and/or the noise associated with MREDs in Scottish waters. A number of suggestions for specific studies are highlighted in the final section of the report.